Constraint qualifications for nonsmooth programming. (2nd December 2018) - Huang, Liren; Tan, Lulin; Liu, Chunguang
ABSTRACT: By using an implicit function theorem and a result of error bound, we provide new constraint qualifications ensuring the Karush–Kuhn–Tuker necessary optimality conditions for both smooth and nonsmooth optimization problems in normed spaces or Banach spaces.